COVID-19's testing of religious roles - Marshall, Katherine (2022)
Societies across the world are tested by the COVID-19 pandemic in countless ways. Deep cracks in social cohesion have become visible in many countries, and many fall along religious lines. Post-COVID-19 policy needs to address robustly what inclusion means both for government policy and for each society.